Establishment of an Efficient Genome Editing System in Lettuce Without Sacrificing Specificity - Pan, Wenbo; Liu, Xue; Li, Dayong; Zhang, Huawei (Frontiers in Plant Science, 2022)
The efficiency of the CRISPR/Cas9 genome editing system remains limited in many crops. Utilizing strong promoters to increase the expression level of Cas9 are commonly used to improve the editing efficiency. However, these strategies also increase the risk of off-target mutation. Here, we developed a new strategy to utilize IME (intron-mediated enhancement)-assisted 35S promoter to drive Cas9 and sgRNA in a single transcript, which increases the editing efficiency by moderately enhancing the expression of both Cas9 and sgRNA. In addition, we developed another strategy to enrich cells highly expressing Cas9/sgRNA by co-expressing the developmental regulator gene GRF5, which has been proved to improve the transformation efficiency, and the transgenic plants from these cells also exhibited increased editing efficiency. This system increased the genome editing efficiency from 14%~28% to 54%~81% on 3 targets tested in lettuce (Lettuce sativa) without increasing the off-target editing efficiency. Thus, we established a new genome editing system with highly improved on-target editing efficiency and without obvious increasement in off-target effects, which can be used to characterize genes of interest in lettuce and other crops.